Memories from school and the formation of identity: The transformative role of (literary) theory - Kolarić Ana (Glasnik Etnografskog Instituta SANU, 2025)
The focus of this text is on the written “testimonies”, or memories, of several literature students, in which they talk about the formation of identity at school. All students attended the elective course “Literary Terms and the Study of Culture” at the Faculty of Philology, University of Belgrade. The course syllabus specifies that one class will cover a chapter from the book Common Schools/Different Identities by Walter Feinberg, an article by Nenad Velicković on the evaluation and selection of textbooks in Bosnia and Herzegovina, and an analysis of specific examples from textbooks for the Serbian language and literature published in the first decade of the 21st century. In their recorded memories, the students connected the problems and themes from the aforementioned texts, as well as examples from the textbooks, with specific events that occurred in their schools, as well as outside the classroom. The personal experiences of students represent possible reactions to the dominant ideas and values offered in textbooks and school curricula in general.